Turnover Intention of Private Sector School’s Librarian In the Capital of Pakistan - Rani Shaista Kanwal (STIM LASHARAN JAYA MAKASSAR, 2019)
This Study will commence to reconnoiter the main cause of turnover intention of Private sector School’s Librarian. The theme is to cadre that issues and gives measure to reduce the turnover intention of employees. How diverse factors tend to predict job satisfaction like reward, motivation, stress, poor management and work environment. We will begin by scrutinizing the people why they leave job so early is there any individual factor or contribution of institutions factors. Next, we will explain the data used, methods and variables chosen for our model. The idea is based on a survey taken by questionnaire to various librarian who is functioning in a Private’s school. In order to get the dependable results, a comprehensive statistical analysis is made on a distributed data set in computer simulation via analytical software. The obtainable results clearly list that those factors are lot of importance in turnover intention